Influence of Turbulent Scalar Mixing Physics on Premixed Flame Propagation. (6th September 2011) - Kolla, H.; Swaminathan, N.
Abstract : The influence of reactive scalar mixing physics on turbulent premixed flame propagation is studied, within the framework of turbulent flame speed modelling, by comparing predictive ability of two algebraic flame speed models: one that includes all relevant physics and the other ignoring dilatation effects on reactive scalar mixing. This study is an extension of a previous work analysing and validating the former model. The latter is obtained by neglecting modelling terms that include dilatation effects: a direct effect because of density change across the flame front and an indirect effect due to dilatation on turbulence-scalar interaction. An analysis of the limiting behaviour shows that neglecting the indirect effect alters the flame speed scaling considerably when u ′ / s L o is small and the scaling remains unaffected when u ′ / s L o is large. This is evident from comparisons of the two models with experimental data which show that the quantitative difference between the two models is as high as 66% at u ′ / s L o = 0.3 but only 4% at u ′ / s L o = 52.4 . Furthermore, neglecting the direct effect results in a poor prediction of turbulent flame speed for all values of u ′ / s L o, and both effects are important for practically relevant values of this velocity ratio.